2022
DOI: 10.3390/pharmaceutics14030569
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Polymeric Micelles for Rapamycin Skin Delivery

Abstract: Facial angiofibromas (FA) are one of the most obvious cutaneous manifestations of tuberous sclerosis complex. Topical rapamycin for angiofibromas has been reported as a promising treatment. Several types of vehicles have been used hitherto, but polymeric micelles and especially those made of d-α-tocopherol polyethylene glycol 1000 succinate (TPGS) seem to have shown better skin bioavailability of rapamycin than the so far commonly used ointments. To better understand the influence of polymeric micelles on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…The results showed no trace amount of rapamycin in the rapamycin‐texosomes group. In a study by Guyader et al., they evaluated rapamycin‐unloaded micelle and rapamycin‐loaded micelle by FTIR, and the rapamycin IR spectra were similar to our results 65 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results showed no trace amount of rapamycin in the rapamycin‐texosomes group. In a study by Guyader et al., they evaluated rapamycin‐unloaded micelle and rapamycin‐loaded micelle by FTIR, and the rapamycin IR spectra were similar to our results 65 …”
Section: Discussionsupporting
confidence: 86%
“…In a study by Guyader et al, they evaluated rapamycinunloaded micelle and rapamycin-loaded micelle by FTIR, and the rapamycin IR spectra were similar to our results. 65 Furthermore, the HPLC method for rapamycin and texosome groups showed that we had a symmetric peak shape with good resolution for all the designed groups. In the free rapamycin group, the obtained peak shape is typical and is similar to the study by Rao et al 66 The peak shape similarity in free exosome and texosome groups found no trace amount of rapamycin in the texosome group.…”
Section: Discussionmentioning
confidence: 87%
“…73 Guillaume et al have used cryo-TEM to determine the rapamycin-loaded spherical micelles. 74 There are different architectures and shapes of micellar structures confirmed by using TEM, as reported in the literature. 75,76…”
Section: ■ Results and Discussionmentioning
confidence: 64%
“…They have shown that with change in temperature the morphology of micelles was changed from spherical to prolate ellipsoid . Guillaume et al have used cryo-TEM to determine the rapamycin-loaded spherical micelles . There are different architectures and shapes of micellar structures confirmed by using TEM, as reported in the literature. , …”
Section: Resultsmentioning
confidence: 94%
“…The results showed that rapamycin deposition in the different skin layers ( stratum corneum , viable epidermis, upper and lower dermis) significantly increased with micelle solution 0.2% after 24 h compared with the ointment. Based on these results, Le Guyader et al 46 evaluated the different stability and skin bioavailability of rapamycin in polymeric micelles (created by combining TPGS with a poloxamer P123) and their respective hydrogel solution to define an optimized formulation to effectively treat FA.…”
Section: Resultsmentioning
confidence: 99%